汉语“和”与俄语“И”连词的对比研 - Chen Xi (Journal of Chinese Language and Culture Studies, 2022)
Abstract: This paper compares conjunctions in two different languages: Chinese "和" and Russian "И". Both are coordinating conjunctions, "和" cannot connect sentences, "И" can. In addition to juxtaposition, "Harmony" can also indicate a choice relationship. "И" has a broader meaning, including inheritance, causality, concession, transition, and other relationships. In the thesis, the usage of Chinese "和" and Russian "И", the similarities and differences between these two conjunctions, are also mentioned. It also mentions that each. 摘要: 本论文对两种不同语言的连词进行对比：汉语“和”与俄语“И”。两个都是并列连词，“和”不可以连接句子，“И”可以。 “和”除了并列以外还可以表示选择关系，“И”的意义更广，包括承接、因果、让步、转折等关系。论文中并列汉语“和”和俄语“И”的用法、这两个连词的同点和差异，还提到每个连词有的和它相似的属于另一个词类的同音虚词。